Virus-like Particle Vaccine Expressing the Respiratory Syncytial Virus Pre-Fusion and G Proteins Confers Protection against RSV Challenge Infection - Su-Hwa Lee; Ki-Back Chu; Min-Ju Kim; Jie Mao; Gi-Deok Eom; Keon-Woong Yoon; Md Atique Ahmed; Fu-Shi Quan (Pharmaceutics, 2023)
Respiratory syncytial virus (RSV) causes severe lower respiratory tract disease in children and the elderly. However, there are no effective antiviral drugs or licensed vaccines available for RSV infection. Here, RSV virus-like particle (VLP) vaccines expressing Pre-F, G, or Pre-F and G proteins on the surface of influenza virus matrix protein 1 (M1) were produced using the baculovirus expression system, and their protective efficacy was evaluated in mice. The morphology and successful assembly of VLPs were confirmed by transmission electron microscope (TEM) and Western blot. High levels of serum IgG antibody response were detected in VLP-immunized mice, and significantly higher levels of IgG2a and IgG2b were found in the Pre-F+G VLP immunization group compared to the unimmunized control. Serum-neutralizing activity was higher in the VLP immunization groups compared to the naïve group, with Pre-F+G VLPs demonstrating superior neutralizing activity to the single antigen-expressing VLP groups. Pulmonary IgA and IgG responses were generally comparable across the immunization groups, with VLPs expressing the Pre-F antigen eliciting higher IFN-γ in spleens. The frequencies of eosinophils and IL-4-producing CD4+ T cell populations were substantially lower in the lungs of VLP-immunized mice, with the PreF+G vaccine inducing a significant increase in CD4+ and CD8+ T cells. VLP immunization significantly decreased the viral titer and inflammation in the lungs of mice, with Pre-F+G VLPs conferring the best protection. In conclusion, our present study suggests that the Pre-F+G VLPs could be a potential vaccine candidate against RSV infection.